The Association between Physician Involvement During Pediatric Out-of- Hospital Cardiac Arrest and Patient Outcomes: a Japanese Nation-Wide Observational Study - Otaka, Shunichi; Ohbe, Hiroyuki; Igeta, Ryuhei; Chiba, Takuyo; Ikeda, Shunya; Shiga, Takashi (Cardiology and Cardiovascular Medicine, 2022)
Background: The effectiveness of physician involvement during out-ofhospital cardiac arrest has been shown in adults but remains unknown in pediatric patients. This study aimed to investigate the association between physician involvement during pediatric out-of-hospital cardiac arrest and patient outcomes. Methods: Using a Japanese nationwide database, we identified pediatric patients with out-of-hospital cardiac arrest from January 2005 to September 2017. We used a generalized linear model to compare outcomes between patients with and without physician involvement during pediatric outof- hospital cardiac arrest. The primary outcome was neurologically favourable survival after 1 month. Secondary outcomes were the return of spontaneous circulation and 1-month survival. Results: In total, 24,684 patients were included in this study. In the adjusted analyses, a ‘physician-present’ group showed a lower 1-month neurologically favourable survival rate compared with a ‘physicianabsent’ group (difference, -0.9%; 95% confidence interval [CI] -1.7–- 0.2; P = 0.02). The physician-present group had a higher rate of return of spontaneous circulation than the physician-absent group (difference, 1.4%; 95% CI 0.2–2.5; P = 0.02), but no difference in 1-month survival was observed between the groups (difference, -0.9%; 95% CI -2.0–0.2; P = 0.09). Conclusions: Physician involvement during pediatric out-of-hospital cardiac arrest was associated with lower 1-month neurologically favourable survival rates, although it was associated with a better return of spontaneous circulation than that in the physician-absent group.